Multi-drug Resistant Acinetobacter baumannii: Phenotypic and Genotypic Resistance Profiles and the Associated Risk Factors in Teaching Hospital in Jordan - Mohammad H. Gharaibeh; Yaman M. Abandeh; Ziad A. Elnasser; Shawkat Q. Lafi; Haneen M. Obeidat; Malak A. Khanfar (Elsevier, 2024)
Background: This study aimed to determine the prevalence of Antimicrobial Resistance Genes (ARGs), with a focus on colistin resistance in clinical A. baumannii, as well as the risk factors associated with A. baumannii infection in Jordanian patients. Methods: In total, 150 A. baumannii isolates were obtained from patients at a teaching hospital. The isolates were tested for antimicrobial susceptibility using disc diffusion and microdilution methods. PCR amplification was used to detect ARGs, and statistical analysis was conducted to evaluate the influence of identified risk factors on the ARGs acquisition. Results: More than 90% of A. baumannii isolates were resistant to monobactam, carbapenem, cephalosporins, Fluoroquinolones, penicillin, and β-lactam agents. Moreover, 20.6% of the isolates (n = 31) were colistin-resistant. Several ARGs were also detected in A. baumannii isolates. Univariate analysis indicated that risk factors and the carriage of ARGs were significantly associated P ≤ (0.05) with gender, invasive devices, immunodeficiency, systemic diseases, tumors, and covid-19. Logistic regression analysis indicated seven risk factors, and three protective factors were associated with the ARGs (armA, strA, and strB) P ≤ (0.05). In contrast, tetB and TEM were associated with 2 risk factors each P ≤ (0.05). Conclusion: Our study indicates a high prevalence of MDR A. baumannii infections in ICU patients, as well as describing the case of colistin-resistant A. baumannii for the first time in Jordan. Additionally, the risk factors associated with ARGs-producing A. baumannii infections among ICU patients suggest a rapid emergence and spread of MDR A. baumannii without adequate surveillance and control measures.